Brazilian Dependent Capitalism Under the Hegemony of Financialized Capital - Castro, Lucas Crivelenti e [UNESP] (Sage Publications Inc, 2021)
An analysis of the Brazilian economic history of the past 50 years shows that the accumulation of foreign debt and its subsequent crisis in the 1980s, the ensuing fiscal adjustments with supervision by the International Monetary Fund, the execution of the Real Plan in 1994, the resulting macroeconomic trifecta, and new laws and resolutions have reinforced and expanded Brazil's economic and financial dependency. Since the 1990s, its political-economic relations have been shaped by the principles of a liberal-monetarist economy that is the basis for the accumulation and revaluation of domestic and foreign capital. Uma analise da historia economica brasileira dos ultimos 50 anos mostra que o acumulo da divida externa e sua posterior crise nos anos 1980, os subsequentes ajustes fiscais com supervisoes do International Monetary Fund, a execucao do Plano Real em 1994, a decorrente politica do tripe macroeconomico e as leis e resolucoes, reforcaram e ampliaram a dependencia economico-financeira do Brasil em sua insercao mundial. Desde os anos 1990, o amago das relacoes politico-economicas brasileiras esta gestado por principios doutrinarios de uma economia liberal-monetarista, a qual e a base para a acumulacao e revalorizacao de capital interno e externo.
Keywords: Dependency; Financialization; Economic subordination; Monetarism; Macroeconomic trifecta